Insert the corresponding expression:
(10×1211×9)x+a=
To solve the problem, we need to simplify the expression (10×1211×9)x+a and write it in the form requested in the question.
We begin by using the exponent rule: (ba)n=bnan. Applying this rule here:
<spanclass="katex">(10×1211×9)x+a=(10×12)x+a(11×9)x+a</span>
Next, we can simplify the expression further by applying the power over a product rule: (ab)n=an×bn.
Applying this rule to both the numerator and denominator gives us:
Numerator: (11×9)x+a=11x+a×9x+a
Denominator: (10×12)x+a=10x+a×12x+a
Therefore, the entire expression becomes:
<spanclass="katex">10x+a×12x+a11x+a×9x+a</span>
This matches the given answer. Thus, the solution to the question is:
10x+a×12x+a11x+a×9x+a
10x+a×12x+a11x+a×9x+a